Shocked quartz grains in the early Cambrian Vakkejokk Breccia, Sweden—Evidence of a marine impact. (12th December 2018) - Alwmark, Carl; Ormö, Jens; Nielsen, Arne T.
Abstract: Here we present a study of the abundance and orientation of planar deformation features (PDFs) in the Vakkejokk Breccia, a proposed lower Cambrian impact ejecta layer in the North‐Swedish Caledonides. The presence of PDFs is widely accepted as evidence for shock metamorphism associated with cosmic impact events and their presence confirms that the Vakkejokk Breccia is indeed the result of an impact. The breccia has previously been divided into four lithological subunits (from bottom to top), viz. lower polymict breccia (LPB), graded polymict breccia (GPB), top sandstone (TS), and top conglomerate (TC). Here we show that the LPB contains no shock metamorphic features, indicating that the material derives from just outside of the crater and represents low‐shock semi‐autochthonous bombarded strata. In the overlying, more fine‐grained GPB and TS, quartz grains with PDFs are relatively abundant (2–5% of the grain population), and with higher shock levels in the upper parts, suggesting that they have formed by reworking of more distal ejecta by resurge of water toward the crater in a marine setting. The absence of shocked quartz grains in the TC indicates that this unit represents later slumps associated with weathering and erosion of the protruding crater rim. Sparse shocked quartz grains (<0.2%) were also found in sandstone beds occurring at the same stratigraphic level as the Vakkejokk Breccia 15–20 km from the inferred crater site. It is currently unresolved whether the sandstone at these distal sites is related to the impact or just contains rare reworked quartz grains with PDFs.